Impact of a Digital Power Line Filter in the 2-Global-Flash Multifocal Electroretinogram of Glaucoma Patients Compared to Controls*. (2nd January 2016) - Ledolter, Anna A.; Todorova, Margarita G.; Schoetzau, Andreas; Palmowski-Wolfe, Anja M.
Abstract: Purpose : To assess the effect of a 50 Hz power line digital filter on the response to a 2-global-flash multifocal electroretinogram (mfERG) in primary open angle glaucoma (POAG) compared to control. Materials and methods : A 2-global-flash mfERG (VERIS™) was recorded (23 control, 34 POAG). Eight recordings were noise contaminated: 4 control, 4 POAG. Response averages from the central 10° and 7 surrounding groups were analyzed with and without a 50 Hz digital filter for the following mfERG response epochs: direct component (15–45 ms), 1st (45–75 ms) and 2nd (75–105 ms) induced components. Results : A digital 50 Hz filter had little effect on uncontaminated with noise waveforms but, in noisy recordings, changed the waveform dramatically to resemble uncontaminated waveforms. In controls' 50 Hz-filtered uncontaminated with noise mfERGs differed significantly from unfiltered responses in induced components. Uncontaminated with noise recordings from glaucoma patients did not differ with or without the notch filter ( p  > 0.1 for all three epochs of mfERG). The mfERG response in the central 10°in glaucoma patients differed significantly from controls, whether the notch filter was used or not ( p  < 0.001). Conclusions : A 50 Hz notch filter allows grossly contaminated waveforms to be analyzed in a meaningful manner. With a 50 Hz filter, glaucoma patients still differed significantly from normal.